The influence of vision on sound localization abilities in both the horizontal and vertical planes - Tabry, Vanessa; Zatorre, Robert J.; Voss, Patrice (Frontiers in Psychology, 2013)
Numerous recent reports have suggested that individuals deprived of vision are able to develop heightened auditory spatial abilities. However, most such studies have compared the blind to blindfolded sighted individuals, a procedure that might introduce a strong performance bias. Indeed, while blind individuals have had their whole lives to adapt to this condition, sighted individuals might be put at a severe disadvantage when having to localize sounds without visual input. To address this unknown, we compared the sound localization ability of eight sighted individuals with and without a blindfold in a hemi-anechoic chamber. Sound stimuli were broadband noise delivered via two speaker arrays: a horizontal array with 25 loudspeakers (ranging from -90o to + 90 o; 7.5 o) and a vertical array with 15 loudspeakers (ranging from -45 o to +67.5 o). A factorial design was used, where we compared two vision conditions (blindfold vs. non-blindfold), two sound planes (horizontal vs. vertical) and two pointing methods (hand vs. head). Results show that all three factors significantly interact with one another with regards to the average absolute deviation error. Although blindfolding significantly affected all conditions, it did more so for head-pointing in the horizontal plane. Moreover, blindfolding was found to increase the tendency to undershoot more eccentric spatial positions for head-pointing, but not hand-pointing. Overall, these findings suggest that while proprioceptive cues appear to be sufficient for accurate hand pointing in the absence of visual feedback, head pointing relies more heavily on visual cues in order to provide a precise response. It also strongly argues strongly against the use of head pointing methodologies with blindfolded sighted individuals, particularly in the horizontal plane, as it likely introduces a bias when comparing them to blind individuals.